Meta-Analysis of the Safety and Efficacy of Direct Oral Anticoagulants for the Treatment of Left Ventricular Thrombus - Mounica Vorla; Dinesh K. Kalra (MDPI AG, 2024)
Background: Literature on the preferred anticoagulant for treating left ventricular thrombus (LVT) is lacking. Thus, our objective was to compare the efficacy of DOACs versus warfarin in treating LVT. Methods: Databases were searched for RCTs and adjusted observational studies that compared DOAC versus warfarin through March 2024. The primary efficacy outcomes of interest were LVT resolution, systemic embolism, composite of stroke, and TIA. The primary safety outcomes encompassed all-cause mortality and bleeding events. Results: Our meta-analysis including 31 studies demonstrated that DOAC use was associated with higher odds of thrombus resolution (OR: 1.08, 95% CI: 0.86-1.31, p: 0.46). A statistically significant reduction in the risk of stroke/TIA was observed in the DOAC group versus the warfarin group (OR: 0.65, 95% CI: 0.48-0.89, p: 0.007). Furthermore, statistically significant reduced risks of all-cause mortality (OR: 0.68, 95% CI: 0.47-0.98, p: 0.04) and bleeding events (OR: 0.70, 95% CI: 0.55-0.89, p: 0.004) were observed with DOAC use as compared to warfarin use. Conclusion: Compared to VKAs, DOACs are noninferior as the anticoagulant of choice for LVT treatment. However, further studies are warranted to confirm these findings.